Correlation of Eating Habits and Physical Activity with Obesity Among SMAN 3 Subang Students And Its Review in Islamic Perspective - Camila Irianti Hadi Putri; Fathul Jannah; Muhammad Arsyad (Junior Medical Journal, 2023)
Background: Obesity is a condition of excess fat accumulation and can cause various health problems. Based on the Riskesdas 2018, adolescents aged 16-18 years in Indonesia have a prevalence of obesity and overweight is 13.5%. The incidence of obesity in adolescents in West Java is 4.51%. Subang, one of the areas in West Java, has an incidence rate of obesity in adolescents is 6.01%. Obesity is still a problem that poses a health challenge and can cause various risks of chronic disease. The study aims to determine the correlation between Eating Habits and Physical Activity with Obesity among SMAN 3 Subang students and its review of The Islamic perspective.Methods: This study is an analytical observational quantitative with cross sectional design. 106 11th graders in SMAN 3 Subang were taken as samples by purposive sampling technique.Results: The result of the Chi-square statistical analysis on the correlation between eating habits and obesity shows the value of p=0.000 (p5), whereas the result of the correlation between physical activity shows the value of p= 0.955 (p0,05).Conclusion: There is significant correlation between eating habits and obesity, however there is no correlation between physical activity and obesity.